2012
DOI: 10.1039/c2mb25180a
|View full text |Cite
|
Sign up to set email alerts
|

RWRMDA: predicting novel human microRNA–disease associations

Abstract: Recently, more and more research has shown that microRNAs (miRNAs) play critical roles in the development and progression of various diseases, but it is not easy to predict potential human miRNA-disease associations from the vast amount of biological data. Computational methods for predicting potential disease-miRNA associations have gained a lot of attention based on their feasibility, guidance and effectiveness. Differing from traditional local network similarity measures, we adopted global network similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
328
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(332 citation statements)
references
References 53 publications
4
328
0
Order By: Relevance
“…We implemented local and global LOOCV to evaluate the prediction accuracy of NDAMDA and 6 previous computational models: WBSMDA,20 RLSMDA,24 MCMDA,28 HDMP,21 RWRMDA 19 and MiRAI 22. In LOOCV, each known association was used as the validation sample and the remaining known associations were regarded as the training samples.…”
Section: Resultsmentioning
confidence: 99%
“…We implemented local and global LOOCV to evaluate the prediction accuracy of NDAMDA and 6 previous computational models: WBSMDA,20 RLSMDA,24 MCMDA,28 HDMP,21 RWRMDA 19 and MiRAI 22. In LOOCV, each known association was used as the validation sample and the remaining known associations were regarded as the training samples.…”
Section: Resultsmentioning
confidence: 99%
“…We found that this study extracted a larger number of disease-related miRNAs for most diseases (Figure 4). Furthermore, we compared the results with other miRNA prioritization methods [4]. We extracted the top 50 candidate miRNAs for breast cancer, colonic cancer, and lung cancer ( Figure 5).…”
Section: Prioritization Of Candidate Mirna On Multiple Cancersmentioning
confidence: 99%
“…Chen has proposed a Random Walk with Restart for MiRNA-Disease prediction (RWRMDA). He proposed that the accuracy to determine the disease-related miRNAs increases by using the global network [4]. Chen utilized a semi-supervised classifier based method (miREFScan) to predict novel disease-related interactions between miRNAs and EFs [5].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of bioinformatics and the progress of miRNA-related projects, researches are gradually focused on the function of miRNAs. Existing studies have shown that miRNAs are involved in many important biological processes [15,16], like cell differentiation [17], proliferation [18], signal transduction [19], viral infection [20], and so on. Therefore, it is easy to find that miRNAs have close relationship with various human complex diseases [12,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, using experimental methods to identify miRNA-disease association is expensive and time-consuming. As the miRNA-related theories are becoming more and more common, such as the prediction model about miRNA and disease, the function of miRNA in biological processes, and signaling pathways, new therapies are urgently needed for the treatment of complex disease; it is necessary to develop powerful computational methods to reveal potential miRNA-disease associations [12,15,20,[34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%